2021
DOI: 10.1177/13623613211025895
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic- and sex-based differences in depression symptoms in autistic and neurotypical early adolescents

Abstract: Prevalence rates of depression are higher in autistic youth than neurotypical peers, yet the effects of autism spectrum disorder diagnosis and sex on depressive symptom severity remain incompletely understood, particularly in specific age groups. Using the Children’s Depression Inventory, Second Edition, this study explored diagnostic- and sex-based differences in depressive symptom severity in a sample of 212 autistic and neurotypical early adolescents (10:0–13:5 years). Significant group differences were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 86 publications
(125 reference statements)
2
16
0
Order By: Relevance
“…A recent body of literature on adolescent and adult samples suggests that females with ASD may experience higher rates of depression and other internalizing symptoms compared to males, including anxiety, suicidality and eating disorders (5)(6)(7), although others studies found no sex differences (8,9). Females with ASD also show higher rates of completed suicide than their male counterpart, in contrast to what is reported in non-ASD samples (i.e., completed suicide more frequent in males) (10).…”
Section: Introductionmentioning
confidence: 89%
“…A recent body of literature on adolescent and adult samples suggests that females with ASD may experience higher rates of depression and other internalizing symptoms compared to males, including anxiety, suicidality and eating disorders (5)(6)(7), although others studies found no sex differences (8,9). Females with ASD also show higher rates of completed suicide than their male counterpart, in contrast to what is reported in non-ASD samples (i.e., completed suicide more frequent in males) (10).…”
Section: Introductionmentioning
confidence: 89%
“…Meanwhile, the seemingly reduced outward autistic behaviour over time in some early diagnosed autistic youth, especially girls/women, should not be assumed to simply represent reduced clinical needs. This may result from learned survival strategies in response to contextual demands [16 ▪▪ ,17 ▪ ,65 ▪▪ ], and may come with increasing mental health burden (e.g., anxiety and depression) that is more prominent in girls/women than boys/men [72 ▪ ], corresponding to findings in diagnosed autistic individuals across life-stages and settings [28,73–76].…”
Section: Autism: It's Not Only About Sex/gender Differences – Beyond ...mentioning
confidence: 99%
“…Taken together, it is not surprising that studies have found that autistic girls endorsed more depressive symptoms on the Children's Depression Inventory-2 [84] and that autistic women were more likely to receive a depression diagnosis [85], and reported slightly higher rates of suicidal behaviors [86]. As a result, more girls were found to receive psychiatric emergency services with anxiety problems, suicide, and self-harm, with steep increases during adolescence [15,87].…”
Section: Introductionmentioning
confidence: 99%